Analisis Kebijakan Program Makan Bergizi Gratis dan Implikasinya Terhadap Perbaikan Status Gizi Anak Di Desa Pasar Baru Kecamatan Kaur Selatan Kabupaten Kaur - Medi Afriansah (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
The Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) is a strategic policy of the Indonesian government launched nationally on January 6, 2025 under the leadership of President Prabowo Subianto, aimed at improving the nutritional status of school-age children, pregnant women, and breastfeeding mothers, as well as addressing stunting and malnutrition issues across various regions of Indonesia. This study aims to analyze the implementation of the Free Nutritious Meal Program (MBG) and its impact on improving the nutritional status of school-age children in Pasar Baru Village, South Kaur District, Kaur Regency. Using a descriptive qualitative method with in-depth interviews, observation, and documentation study techniques, the research results show that the MBG program has been well-designed by the National Nutrition Agency (Badan Gizi Nasional) based on Presidential Regulation No. 83 of 2024, but field implementation still faces obstacles such as distribution delays, limited menu variety, and an inconsistent monitoring system. Nevertheless, the program has had a positive impact on increasing children's body weight, improving dietary patterns, and enhancing students' concentration and school attendance.